Desarrollo del proceso de atención de enfermería en paciente con Virus de Inmunodeficiencia Humana más criptocococis cerebral. - Lema Ortiz, Juan Aurelio (2019)
The following case report deals with a male patient diagnosed with human immunodeficiency virus, who states that he has abandoned antiretroviral treatment for which he is more complicated, returns to the home with moderate-intensity holocranial headache, undergoes laboratory tests, and in the results of the lumbar puncture, the presence of yeasts compatible with cryptococcus neoformans is observed, which is diagnosed with cerebral cryptococcus and is immediately admitted to the internal medicine service. The main objective is to design a plan of nursing care interventions, to improve the patient's health status associated with a strict control of the patient's medication. The evaluation will be applied by functional patterns and the methodology based on the Florence Nightingale theory (Environment-Patient), due to the patient's health situation, it is important to maintain it is an adequate environment since it is beneficial for the prevention of opportunistic diseases. At the end of the follow-up, it was noted that this disease brings complications such as headache and abdominal pain, which affected the patient, but with the appropriate nursing care it was possible to control them, with the results of examinations, we observed that the patient evolved favorably. Hospitalized under medical care and with long-acting antiretroviral treatment.